Moral Disengagement as Determinant of Relational Aggression Among Adolescents - Zaqia Bano; Saima Riaz; Muhammad Jabbar, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The present study aimed at finding the predictive relationship between moral disengagement and relational aggression among adolescents. Sample of 612 adolescent students aged from 12-19 years was collected from different schools and colleges of district Gujrat, Pakistan. Two scales; Moral disengagement scale for Adolescents by Riaz & Bano(2018) and Urdu version of diverse adolescent relational aggression Riaz (2014) were used for measuring variables. The findings of the present study revealed significant predictive relation of moral disengagement with relational aggression [R2 =0.327; F (1,607) = 295.362, p<0.01]; diffusion and displacement of responsibility, sub dimension with relational aggression [R2 =0.182; F (1, 608) = 135.060, p<0.01]; advantageous comparison with relational aggression [R2 =0.135; F (1, 608) = 94.823-, p<0.01]; dehumanization with relational aggression [R2 =0.199; F (1, 608) = 151.106, p<0.01]; attribution of blame with relational aggression [R2 =0.134; F (1, 608) = 94.374, p<0.01], moral justification with relational aggression [R2 =0.110; F (1, 608) = 75.088, p<0.01] and euphemistic labeling with relational aggression [R2 =0.054; F (1, 609) = 34.742, p<0.01] .The present study supported the predictive relationship of moral disengagement with relational aggression among adolescents.